2001
DOI: 10.1021/es011182f
|View full text |Cite
|
Sign up to set email alerts
|

Congener-Independent Immunoassay for Microcystins and Nodularins

Abstract: Cyanobacteria (blue-green algae) (e.g., Microcystis and Nodularia spp.) capable of producing toxic peptides are found in fresh and brackish water worldwide. These toxins include the microcystin (MC) heptapeptides (>60 congeners) and the nodularin pentapeptides (ca. 5 congeners). Cyanobacterial cyclic peptide toxins are harmful to man, other mammals, birds, and fish. Acute exposure to high concentrations of these toxins causes liver damage, while subchronic or chronic exposure may promote liver tumor formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(195 citation statements)
references
References 27 publications
3
185
0
1
Order By: Relevance
“…Although the providers of Aphanizomenon flos-aquae based BGAS state that they screen out MC-levels of more than 1.0 Ag/g dw in their products , independent investigations into the MC contamination of BGAS products have demonstrated toxin concentrations of up to 35 Ag/g dw (Gilroy et al, 2000;Lawrence et al, 2001). Although samples with toxin contaminations of more than 10 Ag MC-LR equivalents/g dw are the exception, 8 of 13 blue-green algae products from the German and Swiss markets tested recently have shown more than 1.0 Ag MC-LR equiv./g DW in concurrent analyses carried out with an Adda-ELISA (Fischer et al, 2001) and cPPA (Heresztyn and Nicholson, 2001). Our own studies ) and the study of Lawrence et al (2001) have shown differences in detectable toxin amounts when employing ELISA, PPA and LC-MS/MS.…”
Section: Microcystin: Risk Assessment and Guidance Values For Variousmentioning
confidence: 99%
“…Although the providers of Aphanizomenon flos-aquae based BGAS state that they screen out MC-levels of more than 1.0 Ag/g dw in their products , independent investigations into the MC contamination of BGAS products have demonstrated toxin concentrations of up to 35 Ag/g dw (Gilroy et al, 2000;Lawrence et al, 2001). Although samples with toxin contaminations of more than 10 Ag MC-LR equivalents/g dw are the exception, 8 of 13 blue-green algae products from the German and Swiss markets tested recently have shown more than 1.0 Ag MC-LR equiv./g DW in concurrent analyses carried out with an Adda-ELISA (Fischer et al, 2001) and cPPA (Heresztyn and Nicholson, 2001). Our own studies ) and the study of Lawrence et al (2001) have shown differences in detectable toxin amounts when employing ELISA, PPA and LC-MS/MS.…”
Section: Microcystin: Risk Assessment and Guidance Values For Variousmentioning
confidence: 99%
“…The ELISA method was performed as described by Fischer et al (2001). Briefly, ELISA plates (NUNC MaxiSorp, Denmark) were coated overnight with OVA-ADDA-hemiglutaryl (OVA-ADDA-HG) in 0.05 M sodium carbonate buffer pH 9.6 (50 Al/well, 2.5 Ag/ml) at 20 jC.…”
Section: Determination and Quantification Of Toxinsmentioning
confidence: 99%
“…The detection range (20 -80% inhibition of PP1) of the colorimetric PPA used is 0.9-3.2 mg MC-LR/l with a derived IC 50 of 1.7 mg MC-LR/l. As a structural biological test system, an ADDA-ELISA established by Fischer et al (2001) was used. The limits of quantitation and detection of the ELISA were 0.2 and 0.05 mg/l, respectively.…”
Section: Microcystinsmentioning
confidence: 99%